Invasion Ecology (Teacher Edition). - Krasny, Marianne E. (National Science Teachers Association (NSTA), 2003)
Strange intruders are invading our part of the world, threatening our environment and our economy. These newcomers and their impact on our ecological balance are the focus of Invasion Ecology, a new book that teaches students to investigate the behaviors of nonnative and native species. Studying real-life invaders such as purple loosestrife and Phragmites, students will learn about the links between biology and ecology -- and explore how scientists are fighting these aggressors with biological controls.